Routledge handbook of security studies - Dunn Cavelty, Myriam; Balzacq, Thierry (Routledge, Taylor & Francis Group, 2017)
This revised and updated second edition features over twenty new chapters and offers a wide-ranging collection of cutting-edge essays from leading scholars in the field of Security Studies. The field of Security Studies has undergone significant change during the past 20 years, and is now one of the most dynamic sub-disciplines within International Relations. This second edition has been significantly updated to address contemporary and emerging security threats with chapters on organised crime, migration and security, cyber-security, energy security, the Syrian conflict and resilience, amongst many others. Comprising articles by both established and up-and-coming scholars, The Routledge Handbook of Security Studies provides a comprehensive overview of the key contemporary topics of research and debate in the field of Security Studies. This new edition of the Handbook is a benchmark publication with major importance for both current research and the future of the field. It will be essential reading for all scholars and students of Security Studies, War and Conflict Studies, and International Relations.